L’approche orientée objets dans l’espace - Żłobińska-Nowak, Aleksandra (Neophilologica, 2004)
The subject matter of this article concerns objectivity of lexicographic description. Here objectivity is being associated with the names of “functional” places, in D. Le Pesant’s understanding of the term. The author presents principles of the object-oriented description of lexicosemantic data, according to the concept by W. Banyś. Later on, she distinguishes a couple of basic classes of appropries predicates, which are typical for the locative nouns suggested by D. Le Pesant. The elements of the object-oriented approach are confronted with their counterparts in such lexicographic theories as: I. Melczuk and A.K. Zholkovsky’s frames, J. Pustejovsky’s qualia structure system, G. Gross’s object classes and unique beginners from the WordNet lexical database. In the suggested descriptive scheme of entries the author places results of her own analyses concerning descriptions of names of functional places, in this case-buildings.